2019
DOI: 10.3390/genes10050382
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bacterial Populations in the Ceca of Swine at Two Different Stages and Their Functional Annotations

Abstract: The microbial composition in the cecum of pig influences host health, immunity, nutrient digestion, and feeding requirements significantly. Advancements in metagenome sequencing technologies such as 16S rRNAs have made it possible to explore cecum microbial population. In this study, we performed a comparative analysis of cecum microbiota of crossbred Korean native pigs at two different growth stages (stage L = 10 weeks, and stage LD = 26 weeks) using 16S rRNA sequencing technology. Our results revealed remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
4
7
0
Order By: Relevance
“…LEfSe is a tool for the discovery of biomarker bacteria among various samples by analyzing the abundance of microbes [ 50 ]. We also implemented this tool to analyze the microbial biomarkers in our swine slurry data, and found that Clostridium and Lactobacillus were predominant across the samples and corroborated the earlier findings [ 51 ]. We reported the specific bacterial biomarkers in each week of storage period.…”
Section: Discussionsupporting
confidence: 83%
“…LEfSe is a tool for the discovery of biomarker bacteria among various samples by analyzing the abundance of microbes [ 50 ]. We also implemented this tool to analyze the microbial biomarkers in our swine slurry data, and found that Clostridium and Lactobacillus were predominant across the samples and corroborated the earlier findings [ 51 ]. We reported the specific bacterial biomarkers in each week of storage period.…”
Section: Discussionsupporting
confidence: 83%
“…A similar study in sheep indicated that the abundance of microbial ABC transporters differed between Tibetan and Small Tail Han breeds grown under the same environmental conditions [41]. In addition, the metabolic pathways of carbohydrates (fructose, mannose, and galactose), amino acids (BCAAs, AAAs, and lysine), and lipids (glycerolipid) have been shown to differ among farm animal breeds grown under the standardized feeding conditions [6,[42][43][44][45]. The breed-associated KEGG pathways showed substantial overlap with the breed-associated KOs.…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with a previous report (Yang et al 2018), the LRFI pigs tended to have higher α variety (Chao 1, Sob, Shannon, ACE, Coverage, and PD) than the HRFI pigs, albeit no significant difference in richness or evenness were found between the two groups. The composition of intestinal microorganisms can be influenced by diet, age, host genetics and environmental factors (Benson et al 2010;Buzoianu et al 2012;Kumar et al 2019). Previous studies indicated that there were significant differences in intestinal microbial composition among pigs at different grow stages (Ke et al 2019;Kumar et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The composition of intestinal microorganisms can be influenced by diet, age, host genetics and environmental factors (Benson et al 2010;Buzoianu et al 2012;Kumar et al 2019). Previous studies indicated that there were significant differences in intestinal microbial composition among pigs at different grow stages (Ke et al 2019;Kumar et al 2019).…”
Section: Discussionmentioning
confidence: 99%